Singapore’s State-Enterprise Network in the Gulf Region: Boom, Bane or an Ongoing Game - YEOH, Caroline (Institutional Knowledge at Singapore Management University, 2012)
Singapore’s state-enterprise network has been, and continues to be, at the forefront of Singapore's internationalization efforts; most recently in the city-state's newest area of focus, the Gulf region. This paper, as part of our series on this topic, studies the city-state’s determined efforts to encapsulate economic space for Singapore-based firms to expand beyond the region through a lens on the Singapore government-linked companies (GLCs), in the context of the unique ‘Arabian allure’ of the GCC economies. Our results show that while the government ‘endorsement’ appears to provide a distinct advantage, the strategic advantages created in the Singapore-styled projects remains uncertain; as well, we find that socio-political intricacies in the host environments continue to stymie efforts to import competencies and business practices.